A retrospective study on penalties for judo athletes with visual impairments - Kons, R. L.; de Oliveira Souza Gulias, V. (International Journal of Sport Nutrition and Exercise Metabolism, 2025)
This study investigates the penalties assessed to judo athletes with visual impairments across three Paralympic Games editions (2016, 2020 + 1, and 2024). A retrospective analysis of 583 penalties from 411 athletes was conducted, focusing on factors such as sex, sports class, medal outcomes, and Paralympic editions. The results reveal that bronze medalists received significantly more penalties per match compared with non-medalists (p < .001). In addition, athletes in the B2 and B3 classifications incurred more penalties than those in the B1 classification (p = .006). However, no significant differences were observed based on sex, the new classification system (J1 and J2), or the Paralympic editions (p > .05). These findings suggest that medal outcomes and classification levels influence penalty frequency, while other factors do not have a substantial impact. The study provides valuable perspectives for refining judo competition rules and classification systems to ensure fairness for athletes with visual impairments.